Spondylolysis in Young Athletes: An Overview Emphasizing Nonoperative Management. (24th January 2020) - Goetzinger, Sara; Courtney, Selen; Yee, Kathy; Welz, Matthew; Kalani, Maziyar; Neal, Matthew
Abstract : Lumbar spondylolysis is a unilateral or bilateral defect of the pars interarticularis, an isthmus of bone connecting the superior and inferior facet surfaces in the lumbar spine at a given level. Spondylolysis is common in young athletes participating in sports, particularly those requiring repetitive hyperextension movements. The majority of young athletes are able to return to full sport participation following accurate diagnosis and conservative management, including a structured treatment program. Surgical intervention for isolated pars injuries is seldom necessary. A progressive physical therapy (PT) program is an important component of recovery after sustaining an acute pars fracture. However, there is a paucity of literature detailing PT programs specific to spondylolysis. Here, we provide an overview of the epidemiology, natural history, radiographic evaluation, and management of pars fractures in young athletes. In addition, a detailed description of a physiotherapy program for this population that was developed at a spine center within an academic medical center is provided.